Notes on Human Trials of Transcranial Direct Current Stimulation between 1960 and 1998 - Esmaeilpour, Zeinab; Schestatsky, Pedro; Bikson, Marom; Brunoni, André R.; Pellegrinelli, Ada; Piovesan, Fernanda X.; Santos, Mariana M. S. A.; Menezes, Renata B.; Fregni, Felipe (Frontiers in Human Neuroscience, 2017)
Transcranial direct current stimulation (tDCS) is investigated to modulate neuronal function including cognitive neuroscience and neuropsychiatric therapies. While cases of human stimulation with rudimentary batteries date back more than 200 years, clinical trials with current controlled stimulation were published intermittently since the 1960’s. The modern era of tDCS only started after 1998. This note aims to review methods and outcomes of tDCS studies from old literature with intention of providing new insight for ongoing tDCS trials and development of tDCS protocols. Articles were identified through a search in PubMed and through the reference list from its selected articles. We included only non-invasive human studies that provided controlled direct current and were written in English, French, Spanish or Portuguese before the year of 1998. Fifteen articles met our criteria. The majority were small-randomized controlled clinical trials that enrolled a mean of approximately 26 subjects. Most of the studies(around 83%) assessed the role of tDCS in the treatment of psychiatric conditions, in which the main outcomes were measured by means of behavioral scales and clinical observation, but the diagnostic precision and the quality of outcome monitoring, including adverse events, were deficient by modern standards. Compared to modern tDCS dose, the stimulation intensities used(0.2- 0.8 mA) were lower, however as the electrodes were typically smaller (e.g., 1.26 cm²), the average electrode current density(0.2 mA/cm2) was approximately 4x higher. The number of sessions ranged from one to 120 (median 14). Notably, the stimulation session durations of several minutes to 11 hours (median 4.5 hours) could markedly exceed modern tDCS protocols. Twelve studies out of 15 showed positive results. Only mild side effects were reported. Most of the studies identified were for psychiatric indications, especially in patients with depression and/or schizophrenia, and majority indicated some positive results. Variability in outcome is noted across trials and within trials across subjects, but overall results were reported as encouraging, and consistent with modern efforts, given some responders and mild side effects. The significant difference with modern dose, low current with smaller electrode size and interestingly much longer stimulation duration may worth considering.